Solution structure of an active mini-proinsulin, M2PI: Inter-chain flexibility is crucial for insulin activity - Cho, YS; Chang, SG; Choi, KD; Shin, HC; Ahn, BY; Kim, KS (SPRINGER-VERLAG SINGAPORE PTE LTD, 2000)
M2PI is an active single chain mini-proinsulin with a 9-residue linker containing the turn-forming sequence 'YPGDV' between the B- and A-chains, but which retains about 50% of native insulin receptor binding activity. The refolding efficiency of M2PI is higher than proinsulin by 20-40% at alkaline pH, and native insulin is generated by the enzymatic conversion of M2PI. The solution structure of M2PI was determined by NMR spectroscopy. The global structure of M2PI is similar to that of native insulin, but the flexible linker between the B- and A-chains perturbed the N-terminal A-chain and C-terminal B-chain, The helix in the N-terminal A-chain is partly perturbed and the beta-turn in the B-chain is disrupted in M2PI. However, the linker between the two chains was completely disordered indicating that the designed turn was not formed under the experimental conditions (20% acetic acid). Considering the fact that an insulin analogue, directly cross-linked between the C-terminus of the B-chain and the N-terminus of the A-chain, has negligible binding activity, a flexible linker between the two chains is sufficient to keep binding activity of M2PI, but the perturbed secondary structures are detrimental to receptor binding.